Regime Switching Mechanism during Energy Futures' Price Bubbles - Koy, Ayben (International Journal of Energy Economics and Policy, 2022)
In the last twenty years, many huge ups and downs have been seen in not only oil prices but also in other spot and derivative' energy prices too. This study has two main purposes. The main purpose of the study is to detect bubbles and their beginning and ending dates in energy derivatives futures prices. Crude oil WTI, natural gas, and heating oil monthly prices are analyzed for the period beginning from 1990 to 2018. Following detecting bubbles, Markov Regime Switching Autoregressive (MSAR) models and Markov Regime Switching Vector Autoregressive (MSVAR) models are used to analyze the movement of the regime-switching mechanism between the bubble dates. The general evidence indicates that the switching mechanism during bubble periods has some mutual similarities as generally their direction is to regime 1 as recession with low/negative returns and high volatility. Following positive return periods in energy prices, mostly after the high return/high volatility periods, the market actors might face bubble collapses.